The Influence of Organizational Culture and Movements on the Performance of Civil Servants at the Regional Secretariat Office of North Bolaang Mongondow Regency - Fitri Babay; Sudarsono; Karlina Napu (Journal of Economic, Business, and Administration (JEBA), 2021)
This study aims to: (1) analyze the influence of organizational culture partially on the performance of Civil Servants at the Regional Secretariat Office of North Bolaang Mongondow Regency. (2) To analyze the effect of mutation partially on the performance of Civil Servants at the Regional Secretariat Office of North Bolaang Mongondow Regency. (3) To analyze and determine the influence of organizational culture and simultaneous transfer on the performance of Civil Servants at the Regional Secretariat Office of North Bolaang Mongondow Regency. This research approach is descriptive quantitative through data collection based on questionnaires and documentation. Furthermore, data analysis in this study is multiple regression with the help of SPSS 21. The results of this study indicate that (1) organizational culture has a positive and significant effect on the performance of Civil Servants at the Regional Secretariat Office of North Bolaang Mongondow Regency with a coefficient of determination of 11.30%. (2) Mutations have a positive and significant effect on the performance of Civil Servants at the Regional Secretariat Office of North Bolaang Mongondow Regency with a coefficient of determination of 53.60%. (3) Organizational culture and transfer together have a significant effect on the performance of Civil Servants at the Regional Secretariat Office of North Bolaang Mongondow Regency with a coefficient of determination of 64.90%. While the remaining 35.10% can be explained by other variables not examined in this study such as work motivation, leadership, employee competence, information technology in work and career management for employees.